Development and validation of mathematical model for population estimation of the two-spotted spider mite in soybeans - Ezequiel G. Souza; Antonio J. Steidle-Neto; Daniela C. Lopes; Priscilla T. N. Maia; Marcos A. M. Fadini (Entomological Communications)
The two-spotted spider mite Tetranychus urticae Koch, 1836 (Acari: Tetranychidae) causes bronzing and leaf drop in soybeans, reducing grain production and quality. Using colorimetric measurements in soybean-producing areas can be an alternative for monitoring the mite, aiding in the estimation of field populations. The objective of this study was to estimate the quantity of the two-spotted spider mite in soybeans through colorimetric measurements using the CIE-L*a*b* color space. Soybean plants at the V3 stage were used with 4 treatments (Control=0; T1=30; T2=60; and T3=100 adult female T. urticae per plant), 4 repetitions, and 170 measurements. Regression and variance analyses were performed using Origin Pro 2015 software. Prediction equations were calibrated. Our results show that there was a significant difference for the L*, a*, and ΔE* variables. Regression analyses presented determination coefficient values of 0.87, 0.93, and 0.55 for L*, a*, and b*, respectively. The use of the (a*) variable in the CIE-L*a*b* color space proved effective in distinguishing between infestation levels. The model created to estimate the quantity of mites on soybean leaves has the potential to be applied in soybean production areas with infestations of the two-spotted spider mite.